Open Research - Pitt, Rebecca; de los Arcos, Beatriz; Farrow, Rob; Open Textbook Library (Open Textbook Library, 2016)
If you have an interest in openness, open education, research skills or want to find out more about the impact of Open EducationalResources (OER), then this resource is for you. You could be: Using an OER with students and interested in assessing its impact Facilitating sessions on open practice with students or colleagues and looking for inspiration Working on a research project and wanting to find out more about incorporating open research techniques into your own practice Curious about the benefits and challenges of open research Looking to use open tools in your research Wanting increased impact for your research Interested in open research on OER This resource will help you explore what open research is, how you can ethically and openly share your findings so others can reuse or develop your work, and the role of reflection and open dissemination. Whilst many challenges and issues apply to all aspects of research (for example: choosing an appropriate methodology), open research brings a range of different opportunities and challenges; it's these that we are specifically interested in exploring. What can openness add to the research process?
Introduction -- 1. Open Research -- 2. Ethics in the Open -- 3. Open Dissemination -- 4. Reflecting in the Open -- 5. Final Thoughts -- Appendix
In English.
Description based on online resource
Keywords: Education -- Textbooks; Education, Higher -- Textbooks